2003
DOI: 10.1128/jcm.41.4.1565-1568.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Herpes Simplex Virus and Varicella-Zoster Virus Infections by Real-Time PCR

Abstract: The herpes simplex viruses types 1 and 2 (HSV-1 and HSV-2) and varicella-zoster virus (VZV) can cause life-threatening infections of the central nervous system and lead to severe infections in immunocompromised subjects and newborns. In these cases, rapid diagnosis is crucial. We developed three different real-time PCR assays based on TaqMan chemistry for the LightCycler instrument to detect HSV-1, HSV-2, and VZV. When the TaqMan assays were compared to our in-house nested PCR assays, the test systems had equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 15 publications
5
87
0
Order By: Relevance
“…This discrepancy cannot be explained by a low sensitivity of our detection method for this virus, as the realtime PCR used in the present study and the nested PCR used in the previous reports (42,43) have comparable sensitivities. However, nested PCR is a method that is prone to higher rates of contamination when compared to real-time PCR (44). Recently, the potential roles of both HHV-6A and HHV-6B in neuroinflammatory pathologies were reported, and the mechanisms that might explain virus-induced neuropathogenesis were reviewed by Reynaud et al, who indicated the immunomodulatory role of viral infections potentiating their oncogenesis in GBM (45).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy cannot be explained by a low sensitivity of our detection method for this virus, as the realtime PCR used in the present study and the nested PCR used in the previous reports (42,43) have comparable sensitivities. However, nested PCR is a method that is prone to higher rates of contamination when compared to real-time PCR (44). Recently, the potential roles of both HHV-6A and HHV-6B in neuroinflammatory pathologies were reported, and the mechanisms that might explain virus-induced neuropathogenesis were reviewed by Reynaud et al, who indicated the immunomodulatory role of viral infections potentiating their oncogenesis in GBM (45).…”
Section: Discussionmentioning
confidence: 99%
“…This region of the genome encodes the glycoprotein D (gD) of HSV-2. 8 Relative expression levels were calculated by the relative standard curve method as outlined in the manufacturer's technical bulletin. To allow for comparisons between samples and groups, quantities of all targets in test samples were normalized to the corresponding GAPDH or total RNA levels and expressed as Target Gene normalized to GAPDH or Target Gene normalized to Total RNA.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…The genetic variations were identified in VZV ORFs 1, 21, 22, 50 and 54 (17,19,24,25). By referring to the SNPs in VZV ORFs 1, 21, 50 and 54, the VZV strains could be grouped into 4 genotypes: A, B, C and J.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of VZV was extracted from vesicle fluid from skin lesions using a viral DNA extraction kit (Da An Gene Co., Ltd., of Sun Yat-Sen University, Guangzhou, China). The collected isolates were first detected by nested polymerase chain reaction (PCR) and quantitative PCR, as described by Weidmann et al (19). The results of the nested PCR and quantitative PCR showed that all the collected isolates exhibited the VZV gene.…”
Section: Methodsmentioning
confidence: 99%